Feeling happy - Holmes, Kirsty (New York, NY KidHaven Publishing, 2019)
Learn about the ways people experience feelings of happiness. Nonfiction picture book featuring the character Captain Cheerful focuses on emotional responses and how to embrace them with positivity
Education
1 2 13
Keywords: Emotions -- Juvenile literature; Emotions in children -- Juvenile literature; Happiness in children -- Juvenile literature